2009
DOI: 10.31421/ijhs/15/4/834
|View full text |Cite
|
Sign up to set email alerts
|

Fruit set and yield of pear cultivars as affected by reduced bee pollination period

Abstract: Results of our experiments prove that pear is more or less sensitive to the reduced bee pollination period. However, the reaction (or the sensitivity) of cultivars may be different to the reduced bee pollination. Most cultivars produce much less yield under reduced bee pollination or no yield with the exclusion of bees but in the case of some cultivars total exclusion of bees does not prevent the yield formation and what is more sometimes reduced bee pollination can be resulted in somewhat higher yield than op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…terrestris L., B . ignitus Smith) intentionally introduced into orchards [ 2 , 3 ], and a field investigation demonstrated that the exclusion of pollination by reared honeybees drastically reduced the yield of all tested cultivars of pear [ 4 ]. Due to the large dependence on bees, an understanding of bee behavior in orchards of self-incompatible crops is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…terrestris L., B . ignitus Smith) intentionally introduced into orchards [ 2 , 3 ], and a field investigation demonstrated that the exclusion of pollination by reared honeybees drastically reduced the yield of all tested cultivars of pear [ 4 ]. Due to the large dependence on bees, an understanding of bee behavior in orchards of self-incompatible crops is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, selfincompatibility impedes stable fruit production in many economically important crops such as Rosaceae fruit trees (e.g., apple, pear, apricot), which are therefore highly dependent on pollinating agents to achieve cross-pollination with a different cultivar (pollinizer) necessary to ensure fruit production. Indeed, Rosaceae fruit trees are usually pollinated by either honeybees (A. mellifera) or bumblebees (B. terrestris L., B. ignitus Smith) intentionally introduced into orchards [2,3], and a field investigation demonstrated that the exclusion of pollination by reared honeybees drastically reduced the yield of all tested cultivars of pear [4]. Due to the large dependence on bees, an understanding of bee behavior in orchards of self-incompatible crops is essential.…”
Section: Introductionmentioning
confidence: 99%